Music and performance culture in nineteenth-century Britain : essays in honour of Nicholas Temperley - Zon, Bennett (Music in nineteenth-century Britain., 2012)
This is the first book to focus upon aspects of performance in the broader context of nineteenth-century British musical culture. An introduction explores Nicholas Temperley's vast contribution to musicology, highlighting his seminal importance in creating the field of nineteenth-century British music studies, and a bibliography provides an up-to-date list of his publications, including books and monographs, book chapters, journal articles, editions, reviews, critical editions, arrangements and compositions.